COMPETENCE APPROACH IN AGILE TRANSFORMATION OF EDUCATION ESTABLISHMENT - Bushuyev, S.; Murzabekova, S.; Khussainova, M. (Scientific Journal of Astana IT University, 2021)
The subject of the article is development of project, programs and project portfolios management systems with drivers of innovation in Agile transformation of Education Establishment is considered. Substantial changes in the environment require further research into the effectiveness of the application of existing agile methodologies, knowledge systems and competencies of project managers and their leadership. The foundations of environmental change lie in changing the decision making paradigm in innovation project and programs management in Agile transformation of Education Establishment. The goal is to explore modern approaches to leadership formation when applying agile methodologies of its specificity from the point of view of decision-making processes in project management. The problems of leadership creation and development in the application of agile project management methodologies for the implementation of information and communication systems are considered. The results of studies were conducted on the basis of a competency-based approach modelled by the International Project Management Association. The content model of competency of the leader applying agile management is presented. Conclusion: The Agile leadership and leadership behaviour patterns are formed in a project management behavioural competency system based on agile technology methods and tools. These competencies included: Self-reflection and self-management, Personal integrity and reliability, Personal communication, Relationships and interaction, Leadership, Teamwork, Conflicts and crises, Inventiveness, Reconciliation, and Orientation to results. The patterns of project managers’ behaviour as agile leaders in project product creation and agile project management are explored. The differences in the behaviour patterns of leaders and agile leaders were examined by behavioural competencies within the identified key competency indicators. Such patterns allowed the authors to identify bottlenecks in the application of agile project management methodologies in the context of the development of innovative products of innovation systems.